(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2021)
The Present descriptive review provides a detailed practical approach in conducting the effective patient medication interview. It includes four main areas, 1) the process involved and goals to be achieved, 2) the importance of accurate patient drug history in patient medication history interview, 3) information to be recorded during patient medication history interview and 4) how to conduct patient medication interview in an effective manner. This present review further attempted to give a clear pictorial representation regarding patient medication history interview as well produced a well-documented patient medication history interview form by referring all the available sources and thorough review of all available scientific literature.